Asuhan Keperawatan Pada Ny. M Dengan Gangguan Sistem Persarafan: Stroke Non Hemoragik (SNH) Di Ruang Mawar 1 RSUD dr. Soeselo Kabupaten Tegal - Dewi Robiatul Azizah; Ahmad Zakiudin (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Introduction: Non-Hemorrhagic Stroke (NHS) or ischemic stroke is the most common type of stroke resulting from blood vessel blockage that inhibits oxygen supply to brain tissue. The prevalence of stroke in Indonesia was recorded at 10.9 cases per 1,000 population in 2013 and increased to 70 cases per 1,000 population (equivalent to 7.0%) in 2017. At RSUD dr. Soeselo, Tegal Regency, the prevalence of stroke cases was recorded at 647 people (3.74%) in 2023, 682 people (3.94%) in 2024, and 1,120 people (6.48%) in 2025. These cases frequently cause impairments in physical, emotional, cognitive, and social functioning, necessitating comprehensive care and management. Writing Method: This scientific writing used descriptive narrative methods through a nursing process approach, aiming to describe nursing care in patients with Non-Hemorrhagic Stroke. Results: Four nursing diagnoses were identified in Ny. M with Non-Hemorrhagic Stroke: ineffective cerebral perfusion risk, impaired physical mobility, knowledge deficit, and fall risk. Nursing interventions included intracranial pressure increase management, neurological monitoring, intravenous medication administration, mobilization support, health education, and fall prevention. Conclusion: After two days of nursing implementation, 2 nursing diagnoses were resolved and 2 others were partially resolved: ineffective cerebral perfusion risk via discharge planning delegated to the ward nurse, and impaired physical mobility with discharge planning including recommendations for gradual passive range of motion exercises and continued family involvement in patient care.